2021
DOI: 10.1007/s11356-021-14616-9
|View full text |Cite
|
Sign up to set email alerts
|

Properties of humic acids depending on the land use in different parts of Slovakia

Abstract: Many studies report organic carbon stabilization by clay minerals, but the effects of land use and soil type on the properties of humic acids (HAs) are missing. The aim of the paper is to determine the effects of land use and soil types on the characteristics of HAs, which have a considerable influence on organic matter quality. It was hypothesised that the effect of the land use on HAs properties depends on the particular size distribution. The research was performed in three ecosystems: agricultural, forest,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 71 publications
2
7
0
Order By: Relevance
“…This is evidence of sufficient content of hydrophobic substances to create stable soil aggregates and of the necessary content of hydrophilic components that form the main reserve of readily available nutrients and that are easily distributed throughout the soil profile. In line with the results of Preuße (2000), Dębska et al (2010), Becher et al (2021) and Banach-Szott et al (2021b), the hydrophilic-hydrophobic properties of HAs are related to the degree of humification of organic matter. Based on the obtained results, it is found that the degree of maturity of HA molecules increases with depth.…”
Section: Properties Of Humic Acidssupporting
confidence: 79%
See 1 more Smart Citation
“…This is evidence of sufficient content of hydrophobic substances to create stable soil aggregates and of the necessary content of hydrophilic components that form the main reserve of readily available nutrients and that are easily distributed throughout the soil profile. In line with the results of Preuße (2000), Dębska et al (2010), Becher et al (2021) and Banach-Szott et al (2021b), the hydrophilic-hydrophobic properties of HAs are related to the degree of humification of organic matter. Based on the obtained results, it is found that the degree of maturity of HA molecules increases with depth.…”
Section: Properties Of Humic Acidssupporting
confidence: 79%
“…This makes it possible to determine the degree of maturity of HA molecules (Sanchez--Monedero et al, 2002;Gonet et al, 2007;Canellas et al, 2010;Boguta et al, 2016). It is worth adding that the examined HA molecules had similar H/C ratios to those obtained by Zdenek and Tesarova (2004), Drąg et al (2007) and Banach-Szott et al (2021b). Dergacheva et al (2012) emphasize that the value of the H/C ratio depends on the conditions under which the HAs formed.…”
Section: Properties Of Humic Acidssupporting
confidence: 53%
“…To determine the exact position of the absorption maxima on such spectral curves, the dependence of the first derivative of the optical density on the wavelength is used under the condition dD/dλ = 0 [5]. The presented curves are characterized by a developed maximum in the range of 230-255 nm, which is determined by benzene fragments with a developed auxochromic substituent, for example, with a carboxyl group [1]. There is also a certain jump in the region of 275 nm, which is explained by the presence of phenolic compounds.…”
Section: Research Resultsmentioning
confidence: 99%
“…Both the results of chemical analyses and vegetation experiments indicate the potential usefulness of willow composts as an alternative fertiliser product [25,27,28]. This is particularly important in terms of carbon sequestration [5,14] and stabilization [5,8,9,[46][47][48] of soil organic matter by low-cost, widely used and effective methods of wood-based substance management. While the use of semi-dynamic composting in open piles to process this type of substrate is widely accepted, the most discussed and controversial seem to be the physicochemical parameters [23,46,47] and the effect of the obtained product on plant growth and development.…”
Section: Discussionmentioning
confidence: 99%